Effect of Diapause on Development and Reproduction of White Rice Stem Borer Scirpophaga innotata Walker (Lepidoptera: Pyralidae) - Teddy Suparno (Jurnal Perlindungan Tanaman Indonesia, 1998)
The objective of this study was to determine the effect of diapause on the development and reproduction of white rice stem borer (WRSB), Scirpophaga innotata Walker. During diapause, larvae of the WRSB, progressively decreased in weight at the rate 3.2 mg per week. Larvae lost 50 per cent of their initial body mass and had up to four stationary molts. Larvae became less active, lost pigmentation and leg rudimentary. The longer the larvae remained in diapause, the lighter in weight the emerging moths were, with fewer eggs and oocytes. After 5 months in diapause, the emerging moths weighted about half as much and had about half as many eggs and oocytes (230.0±35.8 egg cells in ovaries) as moths that emerged from nondiapausing larvae.